Aging, inadequacy, and fiscal constraint: The case of Thailand - Phitawat Poonpolkul; Ponpoje Porapakkarm; Nada Wasi (International Studies of Economics, 2024)
Abstract We use an overlapping generations model to study the challenge in developing countries with a large informal sector and aging population. We use Thailand as a case study and incorporate its labor market structure and its public pension system into the calibrated model. Unlike developed countries, workers in developing countries commonly transit from the formal sector to the informal sector, which can be in the early stage of their working life. This labor market feature crucially limits the coverage of the contributory social security (SS) system. We find that 66% of Thai elderly (aged 60 or over) are ineligible for SS annuity benefits because of an insufficient number of years paying into the SS fund. In addition, we use our model to evaluate two schemes to raise the existing universal basic pension income to the poverty line, namely, uniform benefits and pension‐tested benefits. We find that pension‐testing effectively improves the targeting efficiency, and nontrivially lowers the cost of the basic pension income program.